2017
DOI: 10.14512/gaia.26.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Learning and Education for Sustainable Development

Abstract: Is higher education capable of promoting learning for change? Can transformative learning nurture spaces for innovation in education for sustainable development? A call to action from saguf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 9 publications
3
42
0
4
Order By: Relevance
“…We worked in an iterative way and used a process of reflection on practice led by theoretical assumptions, adopting a "reflective practitioner" approach [47,48]. Our pedagogic-didactic argumentation is characterized by a systemic-constructivist understanding of education [30,49] and of learning [50] (p. 86). Our understanding of transformation is based on the German Advisory Council on Global Change's Flagship Report [40] while our definition of change agents is inspired by Hesselbarth and Schaltegger [19], among others.…”
Section: Approach and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We worked in an iterative way and used a process of reflection on practice led by theoretical assumptions, adopting a "reflective practitioner" approach [47,48]. Our pedagogic-didactic argumentation is characterized by a systemic-constructivist understanding of education [30,49] and of learning [50] (p. 86). Our understanding of transformation is based on the German Advisory Council on Global Change's Flagship Report [40] while our definition of change agents is inspired by Hesselbarth and Schaltegger [19], among others.…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Our review also showed that most models do not explicitly include competences to initiate and navigate personal change and learning, which, in our understanding, is fundamental to cope with, and in particular to lead, change [56,57]. Indeed, transformative learning needs to take place both at an individual and a collective level, taking into consideration the interdependency between individual and collective learning processes [49]. Folkman and Zenger [52] are an exception: they explicitly address personal change capabilities, including self-reflection, personal resilience, and role consciousness.…”
Section: Structuring and Comparing Competences For Sd In Hementioning
confidence: 99%
“…Instead, "it seeks to enhance individuals' capacity to engage with more fundamental questions that also apply to other domains of life" [2] (p. 198). In this regard, both researchers working on sustainable consumption [3,4] and ESC scholars [5,6] point to the importance of personal competencies, especially affective-motivational ones, for achieving this goal.…”
Section: Introductionmentioning
confidence: 99%
“…When thinking about implementing the SDGs, higher education institutions (HEIs) have a major responsibility to act as a driving force [18][19][20][21]. Scientifically, the SDG framework is understood neither as a substitute nor as a final solution for the process of critically discussing sustainable development, which remains a basic scientific duty.…”
Section: Introductionmentioning
confidence: 99%